Exploring Religious Terms in Islam: Opportunity and Challenge of Teaching and Learning Islam - Mujazin Mujazin (Jurnal Bintang Pendidikan Indonesia, 2024)
The concept of religious terms are significant for the sake of teaching and learning Islam and pertains to expressions derived predominantly from one or more religious books. This study seeks to delve into the religious terms and expressions present in the book "Islam: A Short History," aiming to scrutinize their types, meanings, and provide examples. Employing a qualitative research approach, the author elaborates on the various religious terms encountered in the book. While previous research has identified and discussed 14 religious terms, it is acknowledged that these terms fall short of encompassing the entire array of religious expressions found in the book. Following a thorough examination of "Islam: A Short History," the author introduces a new term, "owner of the religion," as a necessary addition to address certain religious expressions. This new term emerges from a deliberate departure from the previous term, "supernatural being," due to a perceived misalignment between the type and the provided examples. Furthermore, the research underscores the influence of Arabic on religious terms. Analyzing religious terms in teaching Islam provides significant contributions by fostering understanding, enriching cultural knowledge, and encouraging critical discourse.